Analisis Literasi Digital Peserta Didik Melalui Pemanfaatan Media Pembelajaran Berbasis Android Smart Apps Creator (SAC) Dan Instagram Dalam Pembelajaran Koloid - Yessi, Miokti (Jurnal Riset Pendidikan Kimia (JRPK), 2021)
This study aim to describe the digital literacy of students after using android-based learning media designed using Smart Apps Creator and equipped with Instagram. The research was conducted at SMA Negeri 7 Palangka Raya using qualitative research methods. The android application for colloidal material designed using Smart Apps Creator (SAC) is used as a media for delivering teaching materials and an evaluation tool in the learning process, while Instagram is used as a media for reporting the results of experiment carried out independently by students. Data collection techniques in this study were questionnaires, observations, and interviews. The dimensions of digital literacy analyzed in this study are information, communication, content-creation, safety, and problem solving. The results showed that the students had a very good category on the dimensions of communication, information, and safety, while the dimensions of content-creation and problem solving were categorized as good. Therefore, it can be concluded that the use of learning media based on Android and Instagram can grow and train students' digital literacy. Keywords: digital literacy, Smart Apps Creator, Instagram, Colloids